High-performance flexible self-powered tin disulfide nanoflowers/reduced graphene oxide nanohybrid-based humidity sensor driven by triboelectric nanogenerator. (January 2020) - Zhang, Dongzhi; Xu, Zhenyuan; Yang, Zhimin; Song, Xiaoshuang
Abstract: Flexible self-powered humidity sensors with high response and good flexibility have attracted extensive interest in wearable electronics, motion monitoring and personal healthcare. In this work, we reported a high-performance flexible tin disulfide nanoflowers/reduced graphene oxide (SnS2 /RGO) nanohybrid-based humidity sensor driven by a poly(tetrafluoroethylene) triboelectric nanogenerator (TENG). The humidity sensitive film of SnS2 /RGO was screen-printed on a flexible PET substrate with Au interdigital electrodes. The TENG has a peak-to-peak voltage of 500 V and maximum output power of 378 μW. The tribotronic constant voltage source is achieved by integrating TENG with voltage rectifier and stabilizer circuits to steadily power the humidity sensor. The performance of the self-powered triboelectric humidity sensor (TEHS) at different humidity levels was systematically investigated, which exhibits high steady output voltage (0–24 V), fast response/recovery time (4 s/3 s for 33%RH, 6 s/15 s for 97%RH), wide sensing range (0–97%RH), great stability, and ultralow power consumption (29.78 μW). Furthermore, the TEHS demonstrated the potential ability of monitoring human breath with differ frequency, human cough, and finger approach in various applications for humidity sensing. This work provides a novel thought to design the self-powered humidity sensor, and also proposes the promising applications of TENG for the self-powered electronic devices. Graphical abstract: Image 1 Highlights: A flexible poly(tetrafluoroethylene) triboelectric nanogenerator (TENG) was fabricated and used as energy harvester. A flexible SnS2 nanoflowers/reduced graphene oxide (SnS2 /RGO) nanohybrid based humidity sensor was fabricated. The self-powered triboelectric humidity sensor (TEHS) was proposed by integrating the TENG with the humidity sensor. The TEHS demonstrates excellent humidity sensing properties and ultralow power consumption in a wide RH range. The TEHS is capable of monitoring human breath, cough, and finger approach for multifunctional applications.